Evaluation Analysis of the Use of the TikTok Application Using the System Usability Scale (SUS) Method: Analisis Evaluasi Penggunaan Aplikasi TikTok dengan Menggunakan Metode System Usability Scale (SUS) - Abdillah, Fahriza (Journal of Vocational Education and Information Technology (JVEIT), 2023)
TikTok is a social media platform that offers short videos ranging from 15 seconds to 3 minutes in length. It remains the most widely used social media platform among Indonesian users. This study aims to analyze user ratings of the usability (ease of use) of the TikTok application using the System Usability Scale (SUS) method. Usability assessment is crucial in application development to ensure that users can easily interact with and benefit from the provided features. The scale comprises 10 statements assessed using a Likert scale, ranging from strongly agree to strongly disagree. The collected assessment data will be analyzed quantitatively to gain a deeper understanding of the usefulness of the TikTok application. The data collection technique employed was a questionnaire created using Google Forms and distributed to 30 respondents. The study's results indicate that the TikTok application has acceptable usability, with a grade of "B" and a descriptive rating of "Good," based on the average score of 74 obtained from the questionnaire.